Respons Viabilitas Benih Kopi Arabica (Coffea arabica) terhadap Pelumuran Jamur Trichoderma viride di Pre-nursery - Emi Sopiana; Muhammad Tahir; Albertus Sudirman (Jurnal Agro Industri Perkebunan, 2018)
Indonesia is the fourth largest coffee producing country in the world after Brazil, Vietnam, and Colombia. This study aims to obtain an optimal rate of Trichoderma viride on coffee seed viability, to obtain the highest growth of Arabica coffee clones, and to obtain interaction between rate of Trichoderma viride and Arabica coffee clones on viability of coffee seeds. The research was conducted in Nursery Farm, State Polytechnic of Lampung from October to December 2016. This research use Factorial Randomized Block Design (RBD). The first factor was the Arabica coffee clone i.e. Sigarar Utang clone and S 795 clone.The second factor was the rate of Trichoderma viride fungi culture i.e.O0 (without Trichoderma viride fungi culture), O1 (100 g Trichoderma viride fungi culture), O2 (200 g of Trichoderma viride fungi culture), O3 (300 g of Trichoderma viride fungi culture). The variables observed included seed growth rate, germination rate, cotyledon rupture rate, hypocotyl height, hypocotyl diameter, normal sprouts, leaf area, root dry weight, and leaf dry weight. If there is a significant difference in Î± 0,05, then the test is continue with the LeastSignificanceDifference test (LSD). The best treatment of Trichoderma viride fungi dosage was dosage 200 g can increase seed growth rate for 12 days, germination rate 80,28%, and hypocotyl height 7,15 cm.The highest clonal treatment in the Sigarar Debt clone can increase the height of hypocotyl of 7,15 cm and the leaf area of 14.39 cm2.Â  Â Keywords: Arabica coffee seed, Trichoderma viride fungi culture, seed growth rate